Levels of intracellular HIV-DNA in patients with suppressive antiretroviral therapy. (24th August 2015) - Cuzin, Lise; Pugliese, Pascal; Sauné, Karine; Allavena, Clotilde; Ghosn, Jade; Cottalorda, Jacqueline; Rodallec, Audrey; Chaix, Marie Laure; Fafi-Kremer, Samira; Soulié, Cathia; Ouka, Marlène; Charpentier, Charlotte; et al.
Abstract : Objective: The objective of this study is to study factors associated with HIV-DNA levels in chronically infected patients on long-term suppressive antiretroviral therapy (ART). Design: A cross-sectional, multicentre study of patients receiving ART for more than 3 years, HIV-RNA less than 50 copies/ml for more than 2 years and CD4 + cell count more than 350 cells/μl. Method: Factors associated with low (<150) or high (>1000), compared with intermediate (150–1000 copies/10 6 PBMCs) levels of HIV-DNA were investigated using multinomial logistic regression. Results: Five hundred and twenty-two patients who initiated ART during the chronic phase were included (71% male; median peak HIV-RNA: 4.88 log10  copies/ml, CD4 + cell count nadir: 222 cells/μl). Median ART duration was 13 years [interquartile range (IQR) 7–17], viral suppression was 5.7 years (IQR 3.9–8.5) and 66% of the patients never experienced ART failure. Median HIV-DNA was 323 copies/10 6 PBMCs (IQR, 129–717) with low, intermediate and high levels observed in 28.3, 55.4 and 16.3%, respectively. In multivariable analysis, women were more likely to achieve a low level of HIV-DNA. Each additional year with suppressed HIV-RNA increased the likelihood of low level and decreased the likelihood of high level of HIV-DNA. Peak HIV-RNA higher than 5log10 was always associated with a decreased risk of low and an increased risk of high HIV-DNA. For patients with peak HIV-RNA lower than 5log10, past ART failure was associated with high level of HIV-DNA. Conclusion: Chronically HIV-infected patients with long-term suppressive ART can achieve low total HIV-DNA but one over six still presented HIV-DNA above 1000 copies/10 6 PBMCs despite long-term viral suppression.